Leading teams : 10 challenges, 10 solutions - Flint, Mandy; Hearn, Elisabet Vinberg (Pearson Education, 2015)
Leading Teams is built on the authors' experience of coaching 1,000+ team leaders in over 15 global corporations. They discovered the 10 common challenges holding teams back and the solutions to counter each one. There's a framework for how to lead a team-enhancement workshop, plus supporting plans and templates on their website www.leadingteamsbook.com.